Estudiantes Guaraníes, interculturalidad y educación superior en misiones, Argentina - Nuñez, Yamila Irupé (Comparative Cultural Studies: European and Latin American Perspectives, 2018)
Currently, intercultural education in Latin America, with special regard to indigenous people’s education has come to constitute a particularly relevant field of anthropological inquiry, which encompasses a wide range of subjects (Rebolledo, 2009). In Argentina, the articulation between Anthropology and Education has contributed to produce multiple discourses and texts in the field of social sciences, which inform a variety of research groups and applied projects in educational contexts. As a part of this collective endeavor, this article aims to analyze the most recurring constrictions that the Guaraní People from the State of Misiones (Argentina) face in their effort to access into the State’s Higher Education Level. The data we present was produced during an intensive anthropological fieldwork in Institutions of Higher Education and Guaraní communities in Misiones. We believe that by applying a comparative, critical and denaturalizing perspective, anthropology may assist the study of educational processes where multiple actors and diverse perspectives are taken into account (Rockwell, 2009). In this regard, our current research seeks to ponder about educational experiences within intercultural learning and teaching environments.